Otogenic Brain Abscess in a Child of Third World Country - A Single Stage Transcranial Transmastoid Approach: A Case Report - Apar Adhikari,; Tekendra Khanal,; Rajesh Kumar Yadav,; Bibek Ghimire,; Meenakshi Basnet,; Sanjeev Kumar Thakur,; Prakash Kafle, (Journal of Universal College of Medical Sciences, 2023)
Brain abscess, though not rare, is an uncommon complication of otitis media. We report a case of 12 years old male for chronic ear discharge, throbbing headache and post aural swelling for three weeks. A detailed history and physical examination of the child was performed and a Magnetic Resonance Imaging (MRI) scan was done. A diagnosis of an intracranial abscess, secondary to the chronic otitis media was made. An emergency craniotomy with drainage of brain abscess was planned and performed by the Neurosurgeon. Otolaryngolgoist performed mastoidectomy, in the same setting. After the surgery, post-operative manage- ment was done and the patient was discharged, uneventfully. The complete management in a single sitting of primary cause and resulting complication with no added expenses is the necessity of a poor country citizen.